Effects of second language learning conditions along the implicit/explicit continuum: an extension of Ishikawa (2019) - Ishikawa, Keiichi (Frontiers in Language Sciences, 2024)
This study is an extension of Author's (2019) investigation into the effects of learning the morphological rules of a second language under various learning conditions along the implicit/explicit continuum. It compared outcomes between learners under the attentional (required to attend to targets) and intentional (required to search for rules) conditions and under the incidental and explicit conditions immediately after exposure and after one week. The study also assessed the nature of acquired knowledge using subjective measures of awareness during the testing phases and post-experimental verbal reports. The results demonstrated similar learning effects across the four groups of learners immediately after the learning phase, whereas only intentional learners outperformed incidental learners after one week. The participants developed conscious and unconscious knowledge irrespective of being attentive or intentional during the learning phase. The outcomes of oral production tasks illustrated that knowledge acquired through exposure did not manifest as productive knowledge. The study discussed the results in terms of learning conditions along the continuum of implicitness and explicitness.